Fuzzy-based temperature and humidity control for HVAC of electric vehicle - Ksm Kader Ibrahim, Babul Salam; Mohd Azubir, Nor Aziah; Ahmad, Salmiah; Akmeliawati, Rini; H. M. I., Nizam; Abdul Muthalif, Asan Ghani; Toha, Siti Fauziah; Hassan, Mohd Khair (Elsevier, 2012)
Vehicles are the people's main means of transportation and thermal comfort in the vehicle cabin plays an important role. The heating, ventilating, and air-conditioning (HVAC) operation system in the vehicle cabin decides the degree of comfort, traffic safety as well as health of the occupants. The challenge of designing the HVAC control is to automatically achieve the thermal comfort, regardless of time varying weather conditions. Since most HVAC systems are complex with nonlinearity, distributed parameters, and multivariable therefore many classical controls do not necessarily yield a satisfactory control performance. This paper presents the development of temperature and humidity control strategy for HVAC based on Fuzzy Logic Control (FLC). The goal of the FLC-based temperature control is to satisfy the convergence and equilibrium property. The simulation test results have been shown a satisfactory to control the temperature and humidity.